Chipless Wireless Temperature Sensor for Machine Tools Based on a Dielectric Ring Resonator. (2016) - Sáez, A. Jiménez; Polat, E.; Mandel, C.; Schüßler, M.; Kubina, B.; Scherer, T.; Lautenschläger, N.; Jakoby, R.
Abstract: This paper presents a wireless temperature sensor designed for the monitoring of machine tools, where valuable workpieces are processed and a defective tool can lead to costly damage to the workpiece. Since cutting tools quickly deteriorate at high temperatures, a measurement of the tool's temperature allows monitoring its state. A wireless measurement is advantageous due to the high angular velocities achieved by the tool. The oil used to cool down the tool and the chips coming out of the workpiece shadow the line-of-sight condition necessary for infrared measurements. In addition, temperatures above 200 °C are achieved, making the employment of silicon-based chips hardly feasible. In this paper, the temperature is read from the resonance frequency of a dielectric resonator mounted on the tool by means of radio-frequency backscattering techniques. A successful temperature measurement has been performed up to 300 °C to test the stability of the sensor. Furthermore, system tests have been performed in a real machine tool where the sensor is interrogated from outside the machine tool through its door, with the tool rotating at up to 10, 000 rpm. With this sensor, real-time monitoring of the tool temperature becomes feasible without altering the current workflow of the machine tool.